Seafood Consumption and Anemia Risk Among Pregnant Women in Indonesian Coastal Areas - Purnama Sari, Dwi Kurnia (Journal of Health and Nutrition Research, 2025)
In coastal areas, a less diverse diet is one of the main causes of anemia in pregnant women. This study aims to analyze the correlation between marine resource consumption patterns and the incidence of anemia in pregnant women in coastal areas of Indonesia in the period January 2025, focusing on food intake. This study uses a cross-sectional study design. The population in this study is pregnant women living in coastal areas, totaling 369 pregnant women; the sampling technique used in this study is Simple Random Sampling, totaling 189 respondents. Data collection was conducted using a Food Frequency Questionnaire, which was employed to identify the types and frequency of marine resource consumption over the past month, while the three-day 24-hour dietary recall was used to estimate daily nutrient intake, including iron and other relevant micronutrients. Anemia status was assessed by measuring hemoglobin levels through the Cyanmethemoglobin method. In data analysis, the Spearman test will be used to identify the relationship between marine resource consumption patterns and the incidence of anemia. Based on the results of the Spearman test on pregnant women, the value of Sig. (2-tailed) = 0.033 was obtained, which showed that there was a significant relationship between seafood consumption patterns and the incidence of anemia in pregnant women in coastal areas. study found a significant relationship between seafood consumption patterns and anemia in pregnant women in coastal areas. The presence of non-heme iron and inhibitory compounds in seafood, along with low intake of red meat and liver, increases the risk of anemia.